Antimicrobial resistance profiles of human Brucella melitensis isolates in three different microdilution broths: the first multicentre study in Bosnia and Herzegovina - Arapović, Jurica; Kompes, Gordan; Dedić, Kanita; Teskeredžić, Sanela; Ostojić, Maja; Travar, Maja; Tihić, Nijaz; Delić, Jasminka; Skočibušić, Siniša; Zekiri-Sivro, Minela; Verhaz, Antonija; Piljić, Dilista; et al. (Elsevier BV, 2022)
Brucellosis is a ubiquitous emergent bacterial zoonotic disease causing significant human morbidity in Bosnia and Herzegovina. So far, a high rate of resistant Brucella has been found worldwide. This study prospectively analysed the rates of resistance among human Brucella melitensis strains isolated in Bosnia and Herzegovina.